Determination on the Presence of Aflatoxins and Ochratoxin a of Fungi used in Bioremediation - Bong, Jing Yee (2017)
Pollution was largely caused by the anthropogenic discharge of harmful chemicals which resulted in heavy metal contamination. There are many ways to remove these pollutants but may be expensive and not environmental friendly. Mycoremediation was a preferable method to remove these pollutants because it was cheap, environmental-friendly and possible to completely degrade pollutants. In mycoremediation, fungi were used as a remediation tool to remove metals. However, fungi produced biologically active compound which was toxic to animals and plants called mycotoxins. The objective of this study was to determine the safety usage of several fungi species used in mycoremediation. Nine different species of fungi were tested for the presence of ochratoxin A and aflatoxins which were two common mycotoxins using thin layer chromatography (TLC). The TLC plate was viewed under UV and compare with the standards Rf values of the mycotoxins. It was found that all the fungi species did not produced aflatoxins. Trichoderma sp. was found to produce ochratoxins A but not in others fungi species. Therefore, Trichoderma sp. was shown to be a poor candidate for mycoremediation as it was not safe and the rest of the fungi isolates were potential candidates for mycoremediation.